A Study of Amavatari Rasa and Rasnadi Gugglu in the Management of Amavata W. S. R. to Rheumatoid Arthritis - Sharma, D K; Charak, Sandeep; Mahajan, Amit; Sakhitha, K S (International Research Journal of Ayurveda & Yoga, 2024)
The present study was aimed to assess the effectiveness of Amavatari rasa and Rasanadi guggulu in Amavata and compare the effect of these two preparations in the treatment. A total of 30 patients of Amavata were registered for the present study and were randomly divided into 2 groups. In group A- Amavatari Rasa 125 mg BD per day was given for 14 days, while in group B- Rasnadi Guggulu 250 mg BD per day was given for 14 days. The effect of therapy in both groups was assessed by a specially prepared pro forma. The results of the study showed that both the groups showed significant relief in symptoms; however, comparing the overall effect of the therapies, Amavatari Rasa proved to be more effective than Rasnadi Guggulu.